Pearl : a transcreation of the fourteenth-century Middle English poem - Winter, Joe, 1943- (Sussex Academic Press, 2019)
"Pearl occupies a special place in the English canon. Together with Gawain and the Green Knight and two minor poems, the late fourteenth-century manuscript came to light after nearly 500 years of being tucked away in one private library or another. While Gawain (which may or may not be by the same hand) received early acclaim as a marvellously-written tale of magic and derring-do, Pearl has yet fully to gain the popularity it richly deserves. In terms of psychological discovery, theological debate, and an unmatched technical brilliance in the joint deployment of alliteration and rhyme, it is a thing of wonder. A dream-vision for almost its entire length, Pearl has a direct relation to the narrator's real world. Whether or not the situation it depicts is a fictional one, the poem stands as a commemoration of the deepest personal experience. While the descriptive passages of a heaven-made world are remarkable, the exchange between a grieving man and the "pearl" he has lost and found - pitched almost in terms of a quickfire argument - is irresistible. A young female character, taking her time, demolishes a learned male opponent. Yet love speaks throughout, in a Christian presentation of the struggle to relinquish self-will, so that by the deftest of literary strokes the reader finally is one with the dreamer as he comes to terms with the beauty of what must be"--